Analysis of Drainage Capacity and Rehabilitation Subjected to Rainfall and Reverse Flow of Marengan River as a Main Drain in Sumenep City, Indonesia - Cahya, Evi Nur; Andawayanti, Ussy; Resmani, Eva (Civil and Environmental Science Journal (CIVENSE), 2018)
Land use changing in Sumenep city in recent years has caused runoff in several locations. Therefore, rehabilitations of existing channel to suit the surface runoff are needed. This paper presents capacity determination of existing drainage channels subjected to rainfall with 5-year flood discharge plan and consideration of sea tides effect to Marengan River which crossed Sumenep city. The proposed flood control methods in Sumenep city area was also discussed. The catchment of specified rural area was modelled using SWMM instrument to compare channel conditions before and after rehabilitation. Channel size and height of water level in channel due to rainfall together with the effect of backwater occurred in Marengan River caused by the sea tides was observed during the time. From the analysis, it was found that most of existing secondary drainage channels are uncapable to accommodate rainfall with 5-year flood discharge plan. From the available eight secondary drainage channels outlets, the last three outlets were subjected to reverse flows effect in Marengan River due to sea tides. In order to reduce the occurance of surface runoff inundation, secondary drainage channel rehabilitation was planned at each outlet, and these proven capable to accommodate rainwater runoff and reverse flow as well